Putting agriculture at the forefront of global climate change negotiations - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
On November 7-18, 2016, the twenty-second session of the Conference of the Parties (COP22) under the theme “Africa, Adaptation and Agriculture” will be held in Marrakesh, Morocco. This year’s meeting will focus on countries turning their pledges into specific objectives and strategies to achieve the historic agreement reached in Paris at COP21, which is to cap climate change well below two degrees Celsius of warming in this century. Translating pledges into results will require robust evidence and sustained political will. In many developing countries, evidence and political will converge in the agriculture sector as it has the potential to reduce greenhouse gas (GHG) emission intensity without compromising economic growth.